1595 Instituting Rapid and Semi-rapid COVID-19 Testing Pathways to Facilitate Emergency Surgery. (12th October 2021) - Berezowska, A; Cross, A; Hunt, E; Price, J; Mirfenderesky, M
Abstract: Aim: Defining a patient's COVID-19 status on admission is essential for optimised patient management, safe bed-placement, and flow across the hospital. Perioperative COVID-19 infection is associated with significantly poorer outcomes and may influence a patient's and/or surgeon's decision to proceed. Rapid PCR tests (1-2 hours) for COVID-19 remain the gold-standard, however most NHS Trust's either do not have, or have severely limited access to such testing modalities. Our aim was to introduce a surgical triaging algorithm to conserve rapid testing for immediate surgery, whilst developing a semi-rapid pathway with results available in 12-15 hours for surgery within 24-48 hours. Method: Using quality improvement methodology, based on a 'PDSA' model we introduced a surgical triaging algorithm. Testing options were categorised into rapid, semi-rapid or routine (24 hours). Defined outcomes, as well as primary and secondary drivers were identified. Both the pre-analytical and post-analytical testing pathways were characterised, concentrating on electronic requesting, laboratory transportation and reporting. Five 'PDSA' cycles were performed with immediate audit and feed-back to surgeons after each round. A vetting procedure was also introduced to improve compliance with requesting. Results: Turn-around-times for COVID-19 PCR swabs at our institution improved from 23 hrs:13 minutes at baseline, to 9 hrs:38 minutes for semi-rapids, to < 2 hours for rapid swabs. Conclusions: Adoption of a surgical triaging algorithm ensured prioritisation of rapid and semi-rapid COVID testing based on clinical need. This ensured optimised patient care, safe theatre and anaesthetic Infection Prevention and Control practices, as well as correct post-operative placement.